1986
DOI: 10.1017/s0022172400065281
|View full text |Cite
|
Sign up to set email alerts
|

Restriction enzyme fingerprinting of enterobacterial plasmids: a simple strategy with wide application

Abstract: SUMMARYRestriction enzyme fingerprints were generated from purified plasmid DNA from 324 clinical isolates that belonged to 7 enterobacterial genera and 88 single plasmids in Escherichia coli K 12 according to the following strategy.Purified plasmid DNA was digested with PstI. The number of fragments detected in a 0-8 agarose gel was used to determine which 2 of 6 restriction enzymes including PstI was most likely to provide a fingerprint comprising sufficient fragments to ensure specificity but sufficiently f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The findings from our study confirm those of others (12,13,19) However, other studies have shown that both of these transposons may occur in isolates from the tropics and may contribute to the widespread dissemination of resistant genes between species (8,20). The number of fragments generated by single enzymes is not sufficiently discriminatory to be useful in plasmid classification, but combining the results from two different digests does provide a basis for classification.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The findings from our study confirm those of others (12,13,19) However, other studies have shown that both of these transposons may occur in isolates from the tropics and may contribute to the widespread dissemination of resistant genes between species (8,20). The number of fragments generated by single enzymes is not sufficiently discriminatory to be useful in plasmid classification, but combining the results from two different digests does provide a basis for classification.…”
Section: Discussionsupporting
confidence: 68%
“…Combined enzyme patterns The combination of digest results from more than one enzyme has been shown to be a possible basis for plasmid grouping (12). Table 3 shows the grouping of the plasmids based on a combination of the fragment numbers using Pst I and EcoR I.…”
Section: Restriction Endonuclease Characterization Of Transconjugant mentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmid fingerprinting Fingerprinting of plasmids using a variety of restriction endonucleases is a technique which may extend the results of plasmid profile typing [15]. However, fingerprinting of plasmids in the type strains of the S. enteritidis phage types, using the restriction endonucleases Hind III and Pst I has demonstrated a remarkable degree of homogeneity amongst the plasmids of 38 MDa, identified in 18 of the 27 phage type strains studied [16].…”
Section: Plasmid Typingmentioning
confidence: 99%